Evaluación de la inhibición de escherichia coli sp a partir del desinfectante obtenido por electrólisis de Cloruro de Sodio (2018)
The development of this project was carried out in three phases, in the first one a bibliographic review was made that allowed to identify the variables that affect the evaluation of the inhibition capacity that the obtained oxidizing agent possesses, in order to make a selection of the factors that have the greatest incidence in the process. This allowed building a design of factorial experiments of order 24, which has as factors the concentration of the oxidizing agent and the contact time of this with the sample to be treated. In the second phase, the oxidizing agent was obtained by replicating the conditions obtained in phase I, sodium chloride concentration of 27 g / L, agitation at 300 RPM, current density of 4.84 A and an operating time of 20 minutes by the electrolysis process, reaching a concentration of 3.87 g / L of sodium hypochlorite analyzed as free residual chlorine. In the third phase, the evaluation of the inhibition capacity of the disinfectant obtained using the bacterium Escherichia coli was carried out as a bio-indicator. The oxidizing agent was applied in samples of synthetic water, inoculated with the microorganism until it reached standard 2 of McFarland, by stirring at 150 RPM. Using the techniques of membrane filtration and plate count, it was determined that sodium hypochlorite in concentrations greater than 80 ppm for a minimum time of 15 minutes, has a percentage of inhibition of fecal coliforms of 100%. The results were evaluated by means of a statistical analysis of double-way variance where the incidence of the concentration of the oxidizing agent, the contact time and the interaction of these factors were identified, on the capacity of inhibition that the chlorinated agent possesses.